Determining Key Influences on Patient Ability to Successfully Manage Noncommunicable Disease After Natural Disaster. Issue Volume 34:Issue s1(2019) (May 2019) - Ryan, Benjamin; Franklin, Richard; Burkle, Frederick; Smith, Erin; Aitken, Peter; Leggat, Peter
Abstract : Introduction: Natural disasters often damage the public health infrastructure required to maintain the wellbeing of people with noncommunicable diseases. This increases the risk of an acute exacerbation or complications, potentially leading to a worse long-term prognosis or even death. Disaster-related exacerbations of noncommunicable diseases will continue, if not increase, due to an increasing disease prevalence, sustained rise in the frequency and intensity of disasters, and rapid unsustainable urbanization in disaster-prone areas. However, the traditional focus of public health and disaster systems remains on communicable diseases, despite a low risk. There is now an urgent need to expand the public health response to include noncommunicable diseases. Aim: To explore the key influences on patient ability to successfully manage their noncommunicable disease after a natural disaster. Methods: A survey of people with noncommunicable diseases in Queensland, Australia, collected data on demographics, disease/condition, disaster experience, and primary concern post-disaster. Descriptive statistics and chi-square tests with Bonferroni-adjustment were used to analyze data. Results: There were 118 responses to the survey. Key influences on the ability to self-manage post-disaster were access to medication, medical services, water, treatment and care, power, and food. Managing disease-specific symptoms associated with cardiovascular disease, diabetes, mental health, and respiratory diseases were primary concerns following a disaster. Stress and anxiety, loss of sleep, weakness or fatigue and shortness of breath were common concerns for all noncommunicable diseases. Those dependent on care from others were most worried about shortness of breath and slow healing sores. Accessing medication and medical services were priorities for all patients post-disaster. Discussion: The key influences on successful self-management post disaster for people with noncommunicable diseases must be reflected in disaster plans and strategies. Achieving this will reduce exacerbations or complications of disease and decrease demand for emergency health care post-disaster.